2016
DOI: 10.1155/2016/4087096
|View full text |Cite
|
Sign up to set email alerts
|

The Intoxication Effects of Methanol and Formic Acid on Rat Retina Function

Abstract: Objective. To explore the potential effects of methanol and its metabolite, formic acid, on rat retina function. Methods. Sprague-Dawley rats were divided into 3- and 7-day groups and a control. Experimental groups were given methanol and the control group were provided saline by gavage. Retinal function of each group was assessed by electroretinogram. Concentrations of methanol and formic acid were detected by GC/HS and HPLC, respectively. Results. The a and b amplitudes of methanol treated groups decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Differences in the adaptation kinetics of the different OP wavelets might imply that they are generated by different inner retinal networks. This was first suggested by Wachtmeister [36], and is further supported by a recent study in rats showing different OP peaks to react differently to methanol intoxication (Liu et al [37]). In regards to the influences of adaptation on sinusoidally-modulated flicker ERG responses, we show, for the mouse, that its first harmonic amplitudes decrease during adaptation to high light levels, whereas they increase during adaption to low light levels.…”
Section: Discussionsupporting
confidence: 55%
“…Differences in the adaptation kinetics of the different OP wavelets might imply that they are generated by different inner retinal networks. This was first suggested by Wachtmeister [36], and is further supported by a recent study in rats showing different OP peaks to react differently to methanol intoxication (Liu et al [37]). In regards to the influences of adaptation on sinusoidally-modulated flicker ERG responses, we show, for the mouse, that its first harmonic amplitudes decrease during adaptation to high light levels, whereas they increase during adaption to low light levels.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, the experiment of Chen et al revealed the more pronounced cone damage in the F-ERG recording in rats after a 7 day period of methanol intoxication (Chen et al 2013 ). On the other hand, Liu et al showed no improvement in both scotopic and photopic recordings of ERG in rats performed on the third and seventh day after intoxication (Liu et al 2016 ). In case reports involving human ERG recordings, a and b wave amplitude reduction is typically seen after both acute and chronic methanol exposure (Ingemansson 1984 ; McKellar et al 1997 ; Ruedemann 1962 ), which proves abnormalities in the process of photoreceptor hyperpolarization, as well as depolarization disorders of Muller glial cells with disturbances in transmission between photoreceptors, bipolar cells, and RGCs, respectively (Eells et al 1996 ; McKellar et al 1997 ).…”
Section: Methanol-induced Optic Neuropathy (Me-ion)mentioning
confidence: 99%
“…Importantly, as blood pH decreases, the concentration of non-ionized methanol increases, which determines its increased penetration into tissues and a more extensive range of their damage (Garner et al 1995 ). Moreover, animal studies have shown that despite almost complete metabolism and removal of methanol from the body, the concentration of formic acid simultaneously tends to persist, causing further tissue damage and delayed regeneration of retinal function (Liu et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations